Effect of caffeic acid grafted chitosan loaded quercetin lyophilized powder formulation on avian colibacillosis and tissue distribution - Ren, Xin; Yuan, Sikun; Ren, Juan; Ma, Leying; Liu, Juxiang; Wang, Gengnan (Frontiers in Veterinary Science, 2024)
Quercetin (QR), recognized as a natural antibacterial ingredient, has found widespread application in the poultry industry. This study investigated the bacteriostatic mechanism and evaluated the in vivo inhibitory impact of caffeic acid-grafted chitosan self-assembled micelles loaded quercetin (CA-g-CS/QR) on avian Escherichia coli (E. coli). The findings indicate that the bactericidal mechanism of CA-g-CS/QR exhibits enhanced efficacy compared to QR alone, disrupting bacterial cell walls, disassembling biofilm structures, and impeding essential components necessary for bacterial growth. Following an avian E. coli attack in broilers, CA-g-CS/QR demonstrated the capacity to enhance the population of beneficial bacteria while concurrently decreasing harmful bacteria within the intestinal tract. Moreover, within 3 days of oral administration of CA-g-CS/QR, a significant decrease in Escherichia spp. count was evident, resulting in the restoration of broilers to a healthy state. CA-g-CS/QR proved to be a significant and more efficacious solution than QR alone for avian E. coli disease. Furthermore, CA-g-CS/QR displayed a broader distribution range and higher concentration within the body. Ten metabolites have been identified in the liver for both QR and CA-g-CS/QR. In conclusion, CA-g-CS/QR has demonstrated a notable capacity to enhance in vitro and in vivo bacterial inhibitory effects, providing foundation for the clinical application of QR in combating avian E. coli infections in broilers.